Wearing Facemasks and Maintaining Social Distancing during COIVD-19 among people in the U.S. - Rashmi Thapaliya; Shugofa Dastgeer (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
This survey of 502 U.S. residents explored how people practiced wearing facemasks and maintaining social distancing during the COVID-19 pandemic. Using Health Benefit Model (HBM), the study found that perceived susceptibility, perceived severity, perceived self-efficacy, perceived benefit, and perceived barrier were significant predictors of wearing facemasks while perceived severity, perceived self-Efficacy, and perceived benefit were significant predictors for maintaining social distancing. While women and people with higher education and higher income were more likely to wear facemasks than others, people of 40 years of age and above and those with higher income tended to maintain social distancing more than others. Participants did not have COVID-19 were more likely to wear facemask and maintain social distancing than those who already had the disease.